PERBANDINGAN MODEL PEMBELAJARAN KOOPERATIF LEARNING TIPE GROUP INVESTIGATION DAN TIPE JIGSAW DITINJAU DARI PEMAHAMAN KONSEP PENDIDIKAN PANCASILA SISWA KELAS V SEKOLAH DASAR - Tinguli, Ainun; Sugiati, Andi; Azis, Abdul (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine whether there is a significant difference in students' attitudes toward cooperation and understanding of Pancasila Education concepts when using the Cooperative learning models of Group Investigation and Jigsaw. This research is a quasi-experimental study with a Nonequivalent Control Group Design. The population of this study consisted of fifth-grade students from elementary schools in Cluster IV of Somba Opu District, and the selected sample included fifth-grade students from SDI Mangasa 1 and SDI Mangasa, chosen using cluster random sampling techniques. The data collection technique employed in this study involved a concept understanding test on Pancasila Education, consisting of 7 essay questions. Data analysis techniques used were descriptive statistics and inferential statistics. The results of this study indicate a significant difference in students' understanding of Pancasila Education concepts taught using the Group Investigation model compared to those taught using the Jigsaw model, with a significance value of 0.03 < 0.05. The average understanding score of Pancasila Education concepts in Experimental Class 1 was 83.32, while in Experimental Class 2, it was 71.88.